2004
DOI: 10.1093/ndt/gfh417
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of nonconservative mutations of serum and glucocorticoid-regulated kinase (SGK1) gene in hypertensive and renal patients

Abstract: Based on statistical analysis homozygosity for nonconservative mutations in the coding region of the SGK1 gene is estimated at < 1/300 000 when a white Caucasian population is considered, arguing against an important role of mutations of this coding region in hypertension and hypertension-associated progression of renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…A subsequent study on a similarly small group failed to observe an association of the same gene variant with blood pressure. 6 A most recent study in a very large group of individuals, however, clearly confirmed the association of the SGK1 gene variant with blood pressure and at the same time disclosed that the association was particularly prominent in individuals with hyperinsulinism. 7 This latter observation is in perfect agreement with recent observations in SGK1 knockout mice.…”
Section: Response: Clc-kb Mutation Revisitedmentioning
confidence: 86%
“…A subsequent study on a similarly small group failed to observe an association of the same gene variant with blood pressure. 6 A most recent study in a very large group of individuals, however, clearly confirmed the association of the SGK1 gene variant with blood pressure and at the same time disclosed that the association was particularly prominent in individuals with hyperinsulinism. 7 This latter observation is in perfect agreement with recent observations in SGK1 knockout mice.…”
Section: Response: Clc-kb Mutation Revisitedmentioning
confidence: 86%
“…A subsequent study failed to detect a correlation of the gene variant with blood pressure in patients with renal failure [95]. The association between the gene variant and blood pressure was, however, later confirmed by a study in more than four thousand individuals [70].…”
Section: Discussionmentioning
confidence: 96%
“…In other contemporary studies, the subjects in the study by Busjahn et al [38] were monozygotic twins (n = 252, age 29 8 12 years) and dizygotic twins (n = 140, age 31 8 12 years) and in the study by Trochen et al [39] they were healthy normotensive individuals (n = 167, age 49 8 16 years) and hypertensive individuals (n = 113, age 59 8 17 years). It is possible that polymorphisms in SGK1 influence blood pressure only in certain age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Trochen et al [39] investigated the same 2 polymorphisms, however, and concluded that they do not exert any significant effect on blood pressure in Caucasians. Our study showed that both rs1057293 and rs1743966 are associated with blood pressure in women in their 50s (n = 941; rs1057293: additive p = 0.034, dominant p = 0.0036; and rs1743966: dominant p = 0.036; data not shown).…”
Section: Discussionmentioning
confidence: 99%